Incest: Domestic Sexual Violence against the Girls - Tursilarini, Tateki Yoga (Jurnal Penelitian Kesejahteraan Sosial, 2018)
Incest is a kind of sexual violence conduct that mostly done by close person or related blood, the victims are girls in domestic areas. Children that should get protection and love to grow normally, but they are suffering from violence in domestic areas. This research is to describe the kinds of violence against children and girls, patriarchal value and culture that contribute to incest, and its sttlement. Data resources from local social institution, non-goverment organization, P2TP2A, WCC Aisyiah, RPTC of Bengkulu Social Agency, victims, and victim families. Data were gathered through interview, documentary analysis, and analysed through qualitative-descriptive technique based on incest cases. The result showed that violences against the girls were reflections of patriarchal value system, men domination over girls, and the strong against the weak or subordinated.The settlement were, not all the victims, family and community, having courage to report incest conduct, so the settlement needs serious effort and mindset change to reconstruct community having gender equality. Incest handling needs grand cultural and structural strategy, to combine eight ministres overseeing the case, through law enforcement or any policy and community culture to set up sinergy on handling incest, that needs comprehensive and continuity handling, on the perpretator, family, and incest victims.